INFLUENCE OF READING ABILITY AND VOCABULARY MASTERY ON WRITING SKILLS DESCRIPTIVE TEXT - Dwi Puji Hastuti (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
This research aims to determine: 1)Influence of reading ability and vocabulary mastery together on writing skills descriptive text. 2)Influence of reading ability towards writing skills descriptive text. 3)Influence of vocabulary mastery on writing skills descriptive text. The populations are X-grade students of Private High School as many as 50 respondents were sampled in this research. The research is conducted by survey method, with multiple linear regression research. The results of hypothesis testing obtained the following conclusions: 1)There is a significant impact on the reading ability and vocabulary mastery together on writing skills descriptive text at Private high school students in West Jakarta. This is evidenced by the acquisition of Sig.= 0.020 0.05 and Fcount = 4.235. 2)There is no significant effect of reading ability towards writing skills descriptive text at private high school students in West Jakarta. This is evidenced by the acquisition of Sig.=0.9000.05 and tcount=0.126. 3)There is a significant influence on the vocabulary mastery on writing skills descriptive text at private high school students in West Jakarta. This is evidenced by the acquisition of Sig =0.029 0.05 and tcount = 2.249.